(untitled) (Research, Society and Development, 2021)
Mandibular torus is a slow-growing bone exostosis with well-defined borders, usually oval and bilateral in shape. Diagnosis is made through clinical and radiographic findings. Surgical removal is necessary when there is a prosthetic indication, recurrent trauma, and in rare cases, due to phonetic disorders. The interference in speech caused by the torus, is due to its size and location, which interferes with the usual positioning of the tongue, changing the articulation points, and thus making pronunciation difficult. Therefore, the aim of this study is to report a clinical case of excision of a bilateral mandibular torus due to speech impairment. A 47-year-old male patient sought dental care complaining of bone growth in the mandible. The clinical examination showed a bilateral increase in the lingual region of the mandible, which was unilobular on the right side and trilobular on the left side, measuring approximately 20x20mm. The patient underwent a surgical procedure to remove the torus under local anesthesia. In the 7-day postoperative period, suture dehiscence was observed, as well as traumatic ulcers and pain complaints. The patient reported that he did not pay attention to postoperative care. As a method of treatment of suture dehiscence, a metronidazole paste was used, as well as a laser therapy protocol, ensuring soft tissue healing. After complete healing, in the clinical evaluation, the patient did not present difficulties in pronunciation. Therefore, it is concluded that, although uncommon, the torus, due to its growth, can interfere with the positioning of the tongue and, consequently, with phonetics, which is a plausible indication for the surgical procedure. Once, the normal bony contours of the mandible are re-established, as well as repositioning and lingual function.